11,12 Epoxyeicosatrienoic Acid Rescues Deteriorated Wound Healing in Diabetes - Katharina Sommer (MDPI AG, 2021)
Epoxyeicosatrienoic acids (EET) facilitate regeneration in different tissues, and their benefit in dermal wound healing has been proven under normal conditions. In this study, we investigated the effect of 11,12 EET on dermal wound healing in diabetes. We induced diabetes by i.p. injection of streptozotocin 2 weeks prior to wound creation on the dorsal side of the mouse ear. 11,12 EET was applied every second day on the wound, whereas the control groups received only solvent. Epithelialization was monitored every second day intravitally up to wound closure. Wounds were stained for VEGF, CD31, TGF-β, TNF-α, SDF-1α, NF-κB, and Ki-67, and fibroblasts were counted after hematoxylin-eosin stain on days 3, 6, 9, and 16 after wounding. After induction of diabetes, wounds closed on day 13.00 ± 2.20 standard deviation (SD). Local 11,12 ETT application improved wound closure significantly to day 8.40 ± 1.39 SD. EET treatment enhanced VEGF and CD31 expression in wounds on day 3. It also seemed to raise TNF-α level on all days investigated as well as TGF-β level on days 3 and 6. A decrease in NF-κB could be observed on days 9 and 16 after EET application. The latter findings were not significant. SDF-1α expression was not influenced by EET application, and Ki-67 was significantly less in the EET group on day 9 after EET application. The number of fibroblasts was significantly increased on day 9 after the 11,12 EET application. 11,12 EET improve deteriorated wound healing in diabetes by enhancing neoangiogenesis, especially in the early phase of wound healing. Furthermore, they contribute to the dissolution of the initial inflammatory reaction, allowing the crucial transition from the inflammatory to proliferative phase in wound healing.